THE FORCE AND SIMULATION ANALYSIS OF TRIPOD CONSTANT VELOCITY UNIVERSAL JOINT - ZHENG JiaoJiao; GUO ChangNing; YONG YaoWei; YANG Lei; PENG WeiZhen (Jixie qiangdu)
Based on the three-dimensional model of tripod constant velocity universal joint,considering the offset of the cases,analyzed and calculated the normal force,peripheral force of the roller,and its change rule with rotating angle and swing angle,and also analyzed the axial force,radial force and deflection torque generated by the friction during the transmission. And then,based on the Herzt contact theory and revised coulomb friction model,using ADAMS to do dynamics simulation analysis of those force,The result show that simulation results generally align with theoretical calculation results,the axial force,radial force and deflection torque changed with the swing angle,and under the conditional of a swing angle,those force changed with the rational angle.